(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2022)
Based on the empirical findings correlating disgust with conservatism, most disgust scholars have fed arguments for its moral unreliability and concluded with moral condemnation of this emotion. In this paper, I will examine common arguments about whether relying on disgust in the moral domain is to be considered good or bad. I will problematize the suggestion that we are justified in firmly believing that disgust is an ethically «dumb» – or an ethically «smart» – emotion. It rather seems that moral disgust can be rational or irrational, pro-social or anti-social, liberal or conservative depending on the eliciting contexts, and that such case-by-case conclusions rely on additional meta-ethical premises.